(3GdeLehYI GdCOHjIs - (3eLehYI ef GdeDdajfs
(3ChdgG (B:s
(3ef cJGH GdcGed dCHi GdYHGS eMeO Hf jRjO GdeHQO QMeg Gddg JYGdi hSjYde GdPjf XdehG Ci efbdH jfbdHhf fUH CjG Hbhdg jfbdHhf s
(3BNQgG (B:s
(3cCfg fSH Edi bhdg cfJ ai THGHi cPG hbGd (B: (3aCUHMJ cfJkG hGUHMJ YGLfkG hTQ NUGd GdeQA cfJ hYGLf s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B7632) s
Keywords: (3GdCOHs